Sistem Pendukung Keputusan Pemilihan Pelajar SMK Terbaik Di Kota Medan Menggunakan Metode Weighted Sum Model - Rio Irwansyah; Mesran Mesran (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Decision Support System (DSS) is a system that can assist leaders in making decisions that are accurate and targeted. Many problems that can be solved using SPK, from some of these problems one of which is the Decision Support System Selection of Vocational High School students in Medan. Of the many Vocational High Schools located in the city of Medan in the Education Office, it is certainly very difficult to find the best students from some Vocational High School. This is because every school must have its own advantages and advantages and this will make it difficult for the Education Office to determine the best Vocational High School students. From the problems encountered, the use of a Decision Support System is expected to be the right solution. Because there are several alternatives and criteria that can influence in generating a decision. There are several methods used in building DSS such as, WSM, AHP, TOPSIS, WP, SAW. In this research, the researcher uses the Weighted Sum Model (WSM) method which is believed to solve the problems faced by the Education Office in selecting the best Vocational High School students